Evaluating ginger extract, wild blueberry extract, and polysorbates (PS20, PS80) on Pseudomonas aeruginosa biofilm formation - Mariam Miari; Sari Shawki Rasheed; Nathaline Haidar-Ahmad; Antoine Abou Fayad; Ghassan M Matar (Journal of Infection in Developing Countries)
Introduction: Pseudomonas aeruginosa is a biofilm forming pathogen that challenges clinical and industrial settings. Many natural products and surfactants have been screened and valued for their anti-biofilm capacity. In this study we assessed the inhibitory effect and molecular mechanism of action of ginger extract (Zingiber officinale Rosc.), wild blueberry extract (Vaccinium angustifolium), and polysorbates (PS20/PS80) on biofilm formation.